PENGARUH PEMBERIAN EKSTRAK BUAH PARE (Momordica charantia lynn) TERHADAP KADAR KOLESTEROL DARAH TIKUS WISTAR JANTAN DIABETIK YANG DIINDUKSI ALOKSAN - Gayuh Setyawan; erna sulistyani (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Diabetes mellitus (DM) is a metabolic disease with characteristics of chronic hyperglycemia and glucosuria. This occurs because of abnormalities of insulin secretion, insulin’s function or both. DM almost always followed by the increasing possibility of chronic complications. One complication encountered is hypercholesterolemia. Therefore we need a comprehensive DM therapy. Bitter melon fruit extracts (Momordica charantia lynn) shown to control the metabolism of glucose (hypoglycemic), This is because the extract contains pinsulin working a case of the hormone insulin. In addition there are several opinions and the results of studies suggest that the extract can lower blood cholesterol levels (hypolipidemic). This research carried out aiming to prove the presence or absence of decrease in blood cholesterol levels in diabetic male wistar rats (injected with alloxan) after given a bitter melon fruit extract. The samples in this study were divided into three groups: group I, group II and group III. All samples were injected alloxan to make the mice became diabetic. Blood cholesterol levels after administration of alloxan and three days later were measured and compared. On 3rd day until 6th day Group I was given 1% CMC Na as controlnegative, group II were given extracts of bitter melon fruit and the third group is given glibenclamide as a positive control. On ay-7 cholesterol levels were measured again. The results of data analysis showed that no significant differences in all outcome measures from all groups (Kruskall Wallis> 0.05). From this it was found that 62 hours after injection of alloxan did not have elevated levels of cholesterol and no significant decrease in cholesterol in male rats fed extracts of the fruit of bitter melon 700mg/200gr BB in 4 days.